TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DALAM HAL UPAH MINIMUM - anita nita (DE RECHT (Journal of Police and Law Enforcement), 2024)
The employment relationship between an employee and an employer is actually a civil relationship based on an agreement between both parties to obtain their respective rights and carry out their obligations. These rights and obligations are stated in the work agreement which is made in writing or verbally. The work agreement must clearly regulate working hours and hours, amount of wages, date of payment of wages, overtime pay, health protection, and so on. However, legal protection for workers does not seem to be felt yet, while legal sanctions seem less frightening for entrepreneurs.